The Changing Landscape of Accounting Profession: Challenges and Future Directions in Nigeria - Falase Kolawole; Sulaiman Taiwo Hassan; Joshua Adedapo Daniel; Oyewole Kazeem Adewale (SocioHumania: Journal of Social Humanities Studies, 2026)
This study investigates the practice of the accounting profession with the aim of identifying the key threats and challenges that hinder its development in Nigeria. To achieve this objective, three hypotheses were formulated and tested using the chi-square statistical technique to examine the relationship between identified challenges and the development of accounting practice in the country. The study drew on the perceptions of key stakeholders in the accounting field, namely academic accountants, professional accountants, and accounting regulators. Primary data were collected and analyzed, and the results revealed that the accounting profession is confronted with significant challenges that negatively influence its growth and development. The study concludes that these constraints may pose serious risks to the future advancement of the profession in Nigeria. It therefore recommends that academic and professional accountants should remain committed and proactive in advancing accounting knowledge and practice, while regulatory bodies should ensure objectivity, transparency, and fairness in the formulation and enforcement of accounting standards and regulations